CO2/CH4 and H2/CH4 Gas Separation Performance of CTA-TNT@CNT Hybrid Mixed Matrix Membranes - Regmi, Chhabilal; Ashtiani, Saeed; Hrdlička, Zdeněk; Friess, Karel (Membranes, 2021)
This study explored the underlying synergy between titanium dioxide nanotube (TNT) and carbon nanotube (CNT) hybrid fillers in cellulose triacetate (CTA)-based mixed matrix membranes (MMMs) for natural gas purification. The CNT@TNT hybrid nanofillers were blended with CTA polymer and cast as a thin film by a facile casting technique, after which they were used for single gas separation. The hybrid filler-based membrane depicted a higher CO2 uptake affinity than the single filler (CNT/TNT)-based membrane. The gas separation results indicate that the hybrid fillers (TNT@CNT) are strongly selective for CO2 over CH4 and H2 over CH4. The increment in the CO2/CH4 and H2/CH4 selectivities compared to the pristine CTA membrane was 42.98 from 25.08 and 48.43 from 36.58, respectively. Similarly, the CO2 and H2 permeability of the CTA-TNT@CNT membrane increased by six- and five-fold, respectively, compared to the pristine CTA membrane. Such significant improvements in CO2/CH4 and H2/CH4 separation performance and thermal and mechanical properties suggest a feasible and practical approach for potential biogas upgrading and natural gas purification.
Keywords: mixed matrix membranes; CO2 and CH4 separation; cellulose triacetate polymer; TNT@CNT hybrid fillers